2023
DOI: 10.3390/ijms24108956
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Is Associated with Increased Immune Infiltrates and Both Anti-Tumour and Immune Suppressive Signalling in Muscle-Invasive Bladder Cancer

Abstract: Hypoxia and a suppressive tumour microenvironment (TME) are both independent negative prognostic factors for muscle-invasive bladder cancer (MIBC) that contribute to treatment resistance. Hypoxia has been shown to induce an immune suppressive TME by recruiting myeloid cells that inhibit anti-tumour T cell responses. Recent transcriptomic analyses show hypoxia increases suppressive and anti-tumour immune signalling and infiltrates in bladder cancer. This study sought to investigate the relationship between hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Several studies have shown that HIF-1α induces DC-mediated inflammation and chemokine receptor type 7 (CCR7)-mediated migration of myeloid DCs (mDCs) 60 62 . In contrast, exposure to hypoxia has been shown to either inhibit or exert no effect on the proinflammatory function of DCs 63 , 64 . The HIF-1α level is also elevated in activated neutrophils 65 .…”
Section: The Downstream Effectors Of Mitf In Myeloid Cellsmentioning
confidence: 98%
“…Several studies have shown that HIF-1α induces DC-mediated inflammation and chemokine receptor type 7 (CCR7)-mediated migration of myeloid DCs (mDCs) 60 62 . In contrast, exposure to hypoxia has been shown to either inhibit or exert no effect on the proinflammatory function of DCs 63 , 64 . The HIF-1α level is also elevated in activated neutrophils 65 .…”
Section: The Downstream Effectors Of Mitf In Myeloid Cellsmentioning
confidence: 98%